Abnormal fermentations in table-olive processing: microbial origin and sensory evaluation - Lanza, Barbara (Frontiers in Microbiology, 2013)
The process of transformation of table olives from tree to table is the result of complex biochemical reactions that are determined by the interactions between the indigenous microflora of the olives, together with a variety of contaminating microrganisms from different sources [fiber-glass fermenters, polyvinyl chloride (PVC) tanks, pipelines, pumps, and water], with the compositional characteristics of the fruit. One of the most important aspects of improving the quality of table olives is the use of selected microorganisms to drive the fermentation. These can supplant the indigenous microflora and, in particular, the complementary microflora that are responsible for spoilage of canned olives. In this context, from a technological point of view, a well-characterized collection of microrganisms (lactic acid bacteria, yeast) that can be isolated from the matrix to be processed (the olive fruit) will provide the basis for the development of starter culture systems. These cultures can be fully compatible with the typical products and will guarantee high quality standards. Inoculation of the brine with such selected starter cultures will reduce the probability of spoilage, and help to achieve an improved and more predictable fermentation process. Control of the fermentation processes can thus occur through chemical, chemico-physical and microbiological approaches, and since 2008, also through organoleptic evaluation (COI/OT/MO/Doc. No 1. Method for the sensory analysis of table olives). This last has established the necessary criteria and procedures for sensory analysis of the negative, gustatory and kinaesthetic sensations of table olives, which can also be attributed to abnormal proliferation of microrganisms. It also sets out the system for commercial classification, through assessment of the median of the defect predominantly perceived.